ANALISIS YURIDIS PERATURAN GUBERNUR DKI JAKARTA NOMOR 175 TAHUN 2013 TERHADAP KESADARAN WAJIB PAJAK - Mulyatno, Prihadi (JURNAL ILMIAH LIVING LAW, 2016)
The goverment of DKI Jakarta has been raising Nilai Jual Objek Pajak (NJOP) in 2013. And since on 2014. The reason of raising Njop is adjustment price of land and materials building which continued raise. The problems about raising Njop, most residents/population not pay the tax, because raising the tariff until 140. Because that public awereness and compliance pay the tax. The identification about the riset is 1) how the law effect to awareness and ability to payer property tax at Tanah Abang about raising Njop in 2014? 2) how solve the problem of the awereness, compliance and abilty to pay the tax? The method in this research is normative juridical approach, the law conceived as norms, rules, principles or dogmas/jurisprudence. Normative juridical research, using literature study (review of the literature). In this research, library materials is a basic data research classified as secondry data. Results of the research: 1) raising of property tax the effect is many reseidents difficulties in implementing payed tax, on awareness, and compliance 2:) must have concept that can affect awareness and compliance of tax payers so that the resulting discipline in accordance with its obligation to pay the tax int the taxpayer.